The impact of equity factors on receipt of timely appropriate care for children with suspected malaria in eastern Uganda - David Humphreys; Joan Nakayaga Kalyango; Tobias Alfvén (BMC, 2021)
Abstract Introduction Malaria accounts for more than one-tenth of sub-Saharan Africa's 2.8 million annual childhood deaths, and remains a leading cause of post-neonatal child mortality in Uganda. Despite increased community-based treatment in Uganda, children continue to die because services fail to reach those most at risk. This study explores the influence of two key equity factors, socioeconomic position and rurality, on whether children with fever in eastern Uganda receive timely access to appropriate treatment for suspected malaria. Methods This was a cross-sectional study in which data were collected from 1094 caregivers of children aged 6-59 months on: illness and care-seeking during the previous two weeks, treatment received, and treatment dosing schedule. Additional data on rurality and household socioeconomic position were extracted from the Iganga-Mayuge Health and Demographic Surveillance Site (HDSS) database. A child was considered to have received prompt and appropriate care for symptoms of malaria if they received the recommended drug in the recommended dosing schedule on the day of symptom onset or the next day. Unadjusted and adjusted logistic regression models were developed to explore associations of the two equity factors with the outcome. The STROBE checklist for observational studies guided reporting. Results Seventy-four percent of children had symptoms of illness in the preceding two weeks, of which fever was the most common. Children from rural households were statistically more likely to receive prompt and appropriate treatment with artemisinin-combination therapy than their semi-urban counterparts (OR 2.32, CI 1.17-4.59, p = 0.016). This association remained significant following application of an adjusted regression model that included the age of the child, caregiver relationship, and household wealth index (OR 2.4, p = 0.036). Wealth index in its own right did not exert a significant effect for children with reported fever (OR for wealthiest quintile = 1.02, CI 0.48-2.15, p = 0.958). Conclusions The findings from this study help to identify the role and importance of two key equity determinants on care seeking and treatment receipt for fever in children. Whilst results should be interpreted within the limitations of data and context, further studies have the potential to assist policy makers to target inequitable social and spatial variations in health outcomes as a key strategy in ending preventable child morbidity and mortality.